Promoting Mathematics Students’ Learning Outcome Using Jarimatika Method For Primary School - Dani Firmansyah; Syahrilfuddin Syahrilfuddin; Zariul Antosa (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2018)
This study aims to implementation jarimatika method to promote students’mathematics leraning outcome for elementary school. This study was conductedin class third elementary schools. Design of this research was classroom actionresearch. Based on the results of mathematics learning students obtained data onthe initial score taken from the scores of the first semester Mathematics examstudents before the application of the Jarimatikaini method was 59.62 then thecycle I daily test increased by 13.63 to 73.42 with an increase percentage of22.80%. It can be concluded that the application of the Jarimatika method canimprove the results of third grade elementary school mathematics learning.